Perlindungan Hukum Terhadap Privasi Dan Dampak Sosial Akibat Penyebaran Video Porno di Media Sosial - Helen Tina BR Lumban Batu; Yudi Kornelis (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The government made pornography included in government legal products in 2008, with Law number 44 which was issued to regulate Indonesian society. The government made pornography included in government legal products in 2008, with Law number 44 which was issued to regulate Indonesian society. A qualitative research approach using a literature review was used, involving the collection and analysis of data from library sources relating to the research subject. In addition, the Investigation selects journal sources, organizes and discusses subjects relevant to the research objectives, and compares articles related to this research. In the literature review, the results of descriptive and qualitative research are summarized (summary) using qualitative methods. The widespread distribution of pornography is a problem that cannot be resolved through regulations. Various laws have been enacted to prevent the production of pornography, which has now been criminalized. The use and promotion of sex, partial or full nudity in scenes, sexually explicit gestures, and social activities of female characters usually fall under pornography. Pornography often depicts women, in particular, as highly degrading sexual objects. An immediate cessation of the distribution of pornographic content on social media and a focus on legal protection for victims of such behavior must be emphasized.